Evaluation of cerebral hemispheric contrast transit with intravenous digital subtraction angiography. - Seeger, J F; Carmody, R F; Smith, J R; Ovitt, T W; McNeill, K (American Journal of Neuroradiology, 1983)
Thirty-six patients with varying degrees of stenosis of one internal carotid artery were studied using intravenous digital subtraction angiography, assessing relative hemispheric washin and washout of contrast medium. Ipsilateral delayed contrast transit was seen in 16 of 18 patients with a 70% or greater carotid artery stenosis. Decreased hemispheric peak contrast density was also seen in most of these patients. With further improvements in the computer program and faster imaging rates, intravenous digital subtraction angiography has the capability of providing valuable physiologic data along with anatomic information in patients with suspected cerebral ischemia.